Repeated PSMA-targeting radioligand therapy of metastatic prostate cancer with 131I-MIP-1095 - Afshar-Oromieh, Ali; Haberkorn, Uwe; Zechmann, Christian; Mier, Walter; Kratochwil, Clemens; Spohn, Fabian; Debus, Nils (European journal of nuclear medicine and molecular imaging, 2017)
Purpose Prostate-specific membrane antigen (PSMA)-targeting radioligand therapy (RLT) was introduced in 2011. The first report described the antitumor and side effects of a single dose. The aim of this analysis was to evaluate toxicity and antitumor activity after single and repetitive therapies.Methods Thirty-four men with metastatic castration-resistant prostate cancer received PSMA-RLT with 131I-MIP-1095. Twenty-three patients received a second, and three patients a third dose, timed at PSA progression after an initial response to the preceding therapy. The applied doses were separated in three groups: <3.5, 3.5-5.0 and >5.0 GBq. Antitumor and side-effects were analyzed by blood samples and other clinical data. Follow-up was conducted for up to 5 years.ResultsThe best therapeutic effect was achieved by the first therapy. A PSA decline of ≥50% was achieved in 70.6% of the patients. The second and third therapies were significantly less effective. There was neither an association between the applied activity and PSA response or the time-to-progression. Hematologic toxicities were less prevalent but presented in a higher percentage of patients with increasing number of therapies. After hematologic toxicities, xerostomia was the second most frequent side effect and presented more often and with higher intensity after the second or third therapy.Conclusion The first dose of RLT with 131I-MIP-1095 presented with low side effects and could significantly reduce the tumor burden in a majority of patients. The second and third therapies were less effective and presented with more frequent and more intense side effects, especially hematologic toxicities and xerostomia.
Im Titel ist die Zahl 131 hochgestellt
Gesehen am 13.12.2018